Penggunaan Nama Tiktok pada Aplikasi Tiktok Cash Secara Melawan Hukum Ditinjau dari Undang-Undang Nomor 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik dan Peraturan Pelaksanaanya - Syafira Aisya Kamila; Muhamad Amirulloh; Elisatris Gultom (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Tort against the use of the application name in the Tiktok Cash application is one of the negative impacts of information technology-oriented social and economic activities. This study aims to find the legal responsibility of Tiktok Cash as the administrator of the electronic system operator and government responsibility. The approach method used in this study is the normative juridical research method approach with descriptive-analytical research specifications, mainly describing the laws and regulations associated with legal theories related to the problem of using the name Tiktok in the Tiktok Cash application. The results of the study concluded that the actions carried out by Tiktok Cash application were tort acts stipulated in Article 28 paragraph (1) EIT LAW. In line with Article 15 EIT LAW, Tiktok Cash provider is fault liability for the loss of its users, while the celebrities involved are responsible based on the element of limitation of liability. Furthermore, the form of government responsibility for the practice of using application names is by carrying out cyber patrols and blocking as stipulated in Article 40 of the EIT LAW and Article 97 paragraph (2) Government Regulation No. 71 Year 2019.